Exergy, economic and environmental evaluation of an optimized hybrid photovoltaic-geothermal heat pump system. (15th October 2020) - Kavian, Soheil; Aghanajafi, Cyrus; Jafari Mosleh, Hassan; Nazari, Arash; Nazari, Ashkan
Highlights: Different photovoltaic systems integrated with ground source heat pump was studied. Multi-objective optimization process was applied by the particle swarm algorithm. Energetic and economic benefits were investigated for each system scenarios. Life cycle cost method were evaluated with inflation and interest rate sensitivity. Irreversibility and Carbon dioxide emission of different scenarios were studied. Abstract: This research presents different scenarios of hybrid photovoltaic-geothermal heat pump system that can provide the requirements of the heating and cooling load consumption in a residential building during the year. One of the major purposes of the present study is to explore the optimum contribution of the solar and ground source energies in which the generation energy costs are reasonable with respect to the total costs, lifetime, and energy losses. For this purpose, a numerical dynamic model consisting of different solar photovoltaic (PV) panels of polycrystalline, monocrystalline, and thin-film cells, batteries, inverter, and ground source heat pump (GSHP) was developed using the engineering equation solver and TRNSYS software. In order to reach the best performance of the system, multi- and single-objective optimizations of the life cycle cost and irreversibility were carried out using the particle swarm optimization algorithm considering all effective parameters of the system including surface area, slope, direction of PV panels and battery capacity. Moreover, the optimization tool which was developed in MATLAB software, was adopted for data interaction between TRNSYS and MATLAB. The results indicate that among various scenarios, the optimized hybrid polycrystalline PV system with an area of 35 m 2 and a solar fraction of 31% can be cost-effective up to a 24% inflation rate. Also, the payback period of the optimized hybrid system compared to the regular GSHP is 3 years with the average global costs, while this value is 10 years for Iran's economic situation.